Information Technology Diffusion in Malaysia's Foodservice Industry - Ismail, A.; Zorn, Steffen; Boo, H.C.; Murali, S.; Murphy, J. (Emerald Group Publishing Limited, 2013)
Purpose: The purpose of this paper is to investigate how three organizational factors – affiliation, sufficient capital and company age – related to 323 Malaysian foodservice companies' diffusion of six information technology (IT) applications. The IT applications, basic or advanced, respectively, represent two innovation diffusion levels, adoption and implementation. Design/methodology/approach: This study drew on a survey of chief executive officers, owners, information system/technology managers, operations managers, and account/financial managers in 323 Kuala Lumpur and Selangor foodservice companies. The study conducted logistic regression to examine factors related to the adoption and implementation of IT applications. Findings: IT adoption and implementation related significantly to sufficient capital. Company age and affiliation showed an insignificant relation with adopting and implementing IT applications. Originality/value: To the authors' knowledge, this is the first hospitality study to examine simultaneously the diffusion of basic and advanced IT applications. Most studies investigate the adoption of one or two innovations, such as spreadsheets, web sites, and e‐mail, without considering diffusion stages. This study demonstrates multiple innovations, multiple diffusion stages and multivariate analyses.